2003
DOI: 10.1103/physrevlett.91.136103
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Self-Assembly of Copolymer-Nanoparticle Mixtures Confined between Solid Surfaces

Abstract: Using numerical calculations, we undertake the first morphological studies of mixtures of AB diblocks and nanoparticles that are confined between two hard walls. A complex interplay of entropic and enthalpic interactions drives the nonselective particles to localize at the hard walls and A/B interfaces, causing the mixture to spontaneously self-assemble into particle-decorated lamellae that are oriented perpendicular to the surfaces. The film reveals a periodic array of particle "nanowires" that are separated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(158 citation statements)
references
References 15 publications
3
153
0
1
Order By: Relevance
“…179 In a theoretical study, Lee et al concluded that confinement of a copolymer nanoparticle mixture could result in stable perpendicular lamellae due to a complex interplay of entropic and enthalpic interactions driving nonselective particles to localize at the hard walls and A-B interfaces. 180 Zhou et al were able to achieve a relatively high loading of trioctylphosphine (TOPO) and polyethylene glycol (PEG) coated CdSe nanoparticles in the microdomains of a PS-b-P2VP diblock copolymer, only slightly effecting the self-assembly, while producing a high particle density. 181 In a combined experimental and theoretical study, it was shown that the location of nanoparticles inside block copolymer domains can be tuned even more accurately by changing the period of a chemically patterned substrate used to guide the perpendicular orientation of lamellar microphases to values slightly higher than the equilibrium period or by adding homopolymer.…”
Section: 177mentioning
confidence: 99%
“…179 In a theoretical study, Lee et al concluded that confinement of a copolymer nanoparticle mixture could result in stable perpendicular lamellae due to a complex interplay of entropic and enthalpic interactions driving nonselective particles to localize at the hard walls and A-B interfaces. 180 Zhou et al were able to achieve a relatively high loading of trioctylphosphine (TOPO) and polyethylene glycol (PEG) coated CdSe nanoparticles in the microdomains of a PS-b-P2VP diblock copolymer, only slightly effecting the self-assembly, while producing a high particle density. 181 In a combined experimental and theoretical study, it was shown that the location of nanoparticles inside block copolymer domains can be tuned even more accurately by changing the period of a chemically patterned substrate used to guide the perpendicular orientation of lamellar microphases to values slightly higher than the equilibrium period or by adding homopolymer.…”
Section: 177mentioning
confidence: 99%
“…Recently, Cheyne and Moffit demonstrated the formation of mesoscopic wires and cables via co-assembly of polystyrene-decorated CdSe nanoparticles and a polystyrene-block-poly (ethylene oxide) block copolymer at the water/air interface. 90 Another approach is inspired by the recent theoretical arguments by Balazs and coworkers [91][92][93] that predict that block polymer/nanoparticle mixtures self-organize into hierarchically ordered structures dictated by the size, surface properties and volume fractions of the nanoparticles. Experimentally, Thomas and coworkers found that hydrocarbon-coated gold nanoparticles, with a diameter of 3.5 nm, segregated to the interface between the microdomains of poly(styrene-b-ethylene propylene) (PS-PEP) copolymer, while larger hydrocarbon-coated silica nanoparticles (21.5 nm in diameter) were located at the center of the PEP domains.…”
Section: Rod-type Nanoparticle Assembly At Fluid Interfacesmentioning
confidence: 99%
“…Thus, with appropriate choice of polymers more structured arrangements with improved percolation of CNTs at low fractions might be possible.. Template-controlled assembly of CNTs is a problem relevant not only to nanocomposites, but to other diverse application areas [6]. Self-organization of inorganic nanoparticles in copolymers have been investigated both experimentally [7] and computationally [8,9] and dispersion of stiff rods, somewhat representative of CNTs, have been investigated in fluids and phase-separating fluid mixtures [10].…”
mentioning
confidence: 99%